Reviewing Imam Al-Shafiis Tafsir Ayat Al-Ahkam for Developing Principles of Contemporary Tafsir Literature - Ahmad, Md Mokhter (IIUC Studies, 2016)
Al-Imam Al-Shafi'i is one of the greatest architects of Islamic thought in general and the Qur'anic interpretation in particular. He is the founder of one of the largest denominations based on Islamic Jurisprudence. He made a substantial contribution towards formulating an epistemological methodology for the proper understanding of the Qur'an, especially the Qur'anic verses related to rulings (Ayat al-ahkam), and left a permanent imprint on and legacy for the later Muslim scholars dealing with Quranic tafsir and/or tafsir of Ayat al-ahkam. The Imam devised and developed this methodology at such a juncture of Muslim intellectual exercise when some alien philosophies and doctrines infiltrated into almost all branches of Islamic knowledge. The tafsir literature was no exception. Besides, the emergence of some deviated intellectual outfits from among the Ummah itself virtually challenged and threatened the very fabric, purity, uniqueness and even existence of a distinct Islamic intellectual identity. For substantiating the principles of their thought, these deviant groups heavily relied on the primary normative sources of Islam (i.e., the Qur'an and the Sunnah) and subsequently deducted policies from thereof for running their intellectual denominations. Some of these policies and principles developed thereof were also related to the interpretation of the Qur'an itself. At this time, Al- Imam Al-Shafi'i along with others came forward, developed epistemological methodologies for governing almost all branches of Islamic knowledge including the Qur'anic interpretation, and thus set the course of Islamic thought on right track. The same scenario is again seen everywhere around the globe where the felid of tafsir is further intruded by some obviously alien and un-Islamic philosophical underpinnings. Scores of denominations have already emerged in the Ummah itself which offer such grotesque interpretations for the Qur'an or some of its verses that fall squarely contradictory even to its basic spirit, the fundamental shari'ah principles, and the vivid Prophetic guidelines. Thus the need of the hour is to reassert the methodologies of Al-Imam Al-Shafi'i for the tafsir of the Quran with an avowed objective of evaluating his contribution to this field and investigating into his epistemological principles so that the current deviation in the Qur'anic tafsir may be corrected and a worthwhile methodology for the contemporary interpretation of the Qur'an may be developed. IIUC Studies Vol.10 & 11 December 2014: 09-38